A new study on the end loss effect for parabolic trough solar collectors. (15th March 2015) - Li, Ming; Xu, Chengmu; Ji, Xu; Zhang, Peng; Yu, Qiongfen
Abstract: In this paper, the end loss effect of arbitrary oriented parabolic trough solar collectors (PTC) is analyzed and discussed, the methods to reduce or compensate the end loss effect by extending heat absorber tube, setting a fan-shaped end plane mirror (FS-EPM) at one end of PTC and inclining PTC are studied, relevant optical analyses are performed, the formulae for calculating the optical end loss ratio and the increased optical efficiency of PTC improved with these reduction or compensation methods are given, and the applicable conditions for these methods are discussed. A five-meter long PTC experimental system was used for testing the increased thermal efficiencies of PTC with these methods. The experimental results (increased thermal efficiencies) are agreed with theoretical results (increased optical efficiencies), which proves that these reduction or compensation methods are feasible and effective. All these works can provide some valuable references to the further study and application on high-efficiency trough solar collecting systems. Highlights: The optical analysis on the end loss effect of arbitrary oriented PTC is performance in detail. Relevant methods to compensate the end loss effect of oriented PTC are further studied. The applicability conditions of the compensation methods are analyzed and discussed. Verified the feasibility of the compensation methods by experiments.